Truncated sums for certain restricted partition functions and transformation formulas for basic hypergeometric series - Yao, Olivia X. M. (Revista de la Real Academia de Ciencias Exactas, Físicas y Naturales. Serie A, Matemáticas, 2023)
In 2012, a truncated version for the Euler pentagonal number theorem was established by Andrews and Merca. Since then, a series of papers on the subject have followed. In this paper, using some transformation formulas for basic hypergeometric series, we prove several truncated sums for four restricted partitions: partitions with even parts distinct, partitions into distinct non-multiples of four, (2, 3)-regular partitions and overpartitions into odd parts. In particular, we establish new identities and inequalities for these restricted partition functions.